Synthesis of 3,3-Disubstituted 2-Oxindoles by Deacylative Alkylation of 3-Acetyl-2-oxindoles - Ortega-Martínez, Aitor; Molina, Cynthia; Moreno-Cabrerizo, Cristina; Sansano, José M.; Nájera, Carmen (Synthesis, 2017)
An innovative and efficient monoalkylation and nonsymmetrical 3,3-dialkylation of oxindoles has been achieved. First, the monoalkylation of 3-acetyl-2-oxindoles can be performed in good yields under mild reaction conditions using alkyl halides and benzyltrimethylammonium hydroxide (Triton B) as base at room temperature. This methodology is applied to construct the synthetically challenging compound 1,3-dimethyl-2-oxindole. Subsequent deacylative alkylation (DaA) of the alkylated 3-acetyl-2-oxindoles with alkyl halides takes place efficiently using LiOEt or by conjugate addition with electron-deficient alkenes in the presence of Triton B at room temperature under argon, affording the corresponding unsymmetrically 3,3-disubstituted 2-oxindoles. This simple methodology has been applied to the synthesis of precursors of horsfiline, esermethole, physostigmine, and phenserine alkaloids.
Keywords: deacylation; alkylation; 2-oxindoles; Michael addition; Triton B